Development of Public Value Based E-Government Maturity Framework - Titisari Ramadhane; Luthfi Ramadani; Lukman Abdurrahman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The implementation of E-Government in Indonesia is expected to assist the government in providing services and changing relations with citizens, businesses, and other government agencies. To support the implementation of e-Government, one of the things that can be proposed is the determination of public value in public services. Public value can be defined as the value created by the government for citizens through the delivery of public services. In implementing the SPBE performance targets at the Jombang Regency Communication and Informatics Service, problems were found, including, the Regional Apparatus Organization (OPD) was still building its applications without coordinating, there were still many OPD applications that could not be integrated with other applications and it is still difficult to fulfil sectoral data in OPD, thus affecting the public value obtained by the people in Jombang Regency. The case study focus on assessment of the SiRinduNona website of the Department of Investment and Integrated One-Stop Services Jombang Regency based on the development public value-based E-Government maturity framework that has been made by researchers. The results of the maturity stage of The SiRinduNona website for Jombang Regency is included in stage 4, namely collaboration stage with a percentage of 73.14%.